Generic Design Coastal Erosion Volumes and Setbacks for Australia. June 2012. - Mariani, A; Turner, I L; Flocard, F; Davey, E K; Goodwin, I D; Shand, T D; Carley, J T; Splinter, K (UNSW Sydney, 2012)
UNSW Water Research Laboratory Report No. 247